WAROK REPRESENTATION IN THE ART OF REOG PONOROGO (ANTROPOLINGUISTIC STUDY): REPRESENTASI WAROK DALAM KESENIAN REOG PONOROGO (KAJIAN ANTROPOLINGUISTIK) - Muhamad Agus Prasetyo; Eti Setiawati (LLDIKTI Wilayah X, 2021)
The study purpose is to identify lingual aspect of Tembang Pangkur (TP) and describe its relationship with culture to represent Warok character. Lingual aspects of TP are identified through lexical cohesion, grammatical cohesion, and other language peculiarities, while relationship of TP with culture is described by transcendental theory. This study method is descriptive qualitative with stages, includes data collection, transcripts, analysis, interpretation, and make conclusions. The object as well as data in this study is TP contained in Serat Wedhatama, 12th stanza by K.G.P.A.A. Mangkunegara IV. The TP is often used by Reog cultivators to represent Warok character. The results of the study, including (1) lingual aspect of TP shows a complete relationship of form and meaning until a meaningful causal relationship is obtained, namely if someone wants to become a wong sepuh (Warok) then must receive divine revelation; (2) relationship between TP and culture shows the existence of Sufism teachings whose implementation is formulated with catur sembah. A person who has performed catur sembah can be said to be a wong sepuh. Likewise in the art of Reog Ponorogo, Warok is represented as a wong sepuh as described in TP.